Differentiation of Yersinia enterocolitica serotype O:5,27 strains by phenotypic and molecular techniques. - Fukushima, H (1993)
Restriction endonuclease analyses of virulence plasmid DNA (REAP) and chromosomal DNA and other phenotypic characteristics were used to study the differentiation of Yersinia enterocolitica serotype O:5,27 strains. There was a close correlation between REAP patterns and the geographical distribution of serotype O:5,27. Human isolates produced only one REAP pattern, which was also found with isolates from pigs and dogs.